Expert Playlist Intro Lessons from Amazon, Google, Apple and Other Silicon Valley Giants - O'Reilly, Tim (O'Reilly Media, Inc., 2019)
In this brief introduction to Tim O'Reilly's Expert Playlist, find out why he selected these pieces to study how some of the most advanced companies on the planet not only use technology but build their culture to support it.